HUBUNGAN KEKUATAN CORE STABILITY DENGAN KESEIMBANGAN DINAMIS PADA LANSIA DI PANTI WERDHA BUDI MULIA 3 JAKARTA - Difa Salsabiil Maulidya (2022)
Background :Getting old is a process that occurs naturally and everyone will enter the aging process or the process of getting old. Everyone who enters the age of 60 years or older is usually referred to as the elderly or elderly. At the age of over 60 years or aging will usually affect a change that can result in a person experiencing the risk of falling. These changes will affect balance, flexibility and strength in posture. Strength Core stability is a measurement that increases optimal movement. Strength Core stability is also good for improving movement performance in order to prevent injury. This decreased balance in the elderly is a problem and causes the risk of falls in the elderly population, especially in the dynamic balance needed to help smooth walking activities. The purpose of this study was to determine the relationship between the strength of core stability and dynamic balance in the elderly. The research method in this scientific paper is a cross-sectional study. The measuring instrument used in this study is dynamic balance using the Timed up and Go test. Based on the measurement results from SPSS with a correlation test using Spearmen's Rho, the p value = -0.188 was obtained. The conclusion from these results is that there is no correlation between the strength of core stability and the dynamic balance of the elderly.